Evolution of Infant Mortality in Chile and How It Has Been Reflected in Scientific Publications Between 1980 and 2019 - Vanegas-Lopez, J (SOC ARGENTINA PEDIATRIA, 2021)
Introduction. One of the Millennium Development Goals is to reduce the child mortality rate (CMR), an indicator still present in the Sustainable Development Goals (2015-2030). At the same time, scientific investigations and reports were necessary to assess the behavior of the infant mortality rate (IMR) and the effectiveness of interventions to approach it. Objective. To describe IMR behavior in Chile and how it has been reflected in the scientific publications made in the 1980-2019 period. Material and methods. Implementation of the multivariate adaptive regression spline (MARS) method in relation to IMR between 1980 and 2016, and search for related articles published between 1980 and 2019 in SciELO, Lilacs, PubMed, Cochrane Library, and Embase. The analysis included IMR behavior and its reflection in the publications made in that period. Results. IMR decreased from 28 % to 7.2 % per 1000 live births between 1980 and 2016 (-74 %) and 82 publications were identified in this period. Two types of studies about IMR were reported as of the cutoff point of 1996. In the first period, studies focused on preventable diseases and interventions, while IMR showed a slowing down in its reduction. After the cutoff point, studies focused on non-preventable diseases and factors related to inequalities and inequities. Conclusions. IMR prevails as a synthetic indicator of health conditions. Changes in its evolution and causes have been reflected in publications, which have shifted their focus and areas of interest in accordance with the changes in this indicator.